Synthesis of sp3-Enriched β-Fluoro Sulfonyl Chlorides - Gurbanov, Rustam; Sokolov, Andriy; Golovach, Sergey; Melnykov, Kostiantyn; Dobrydnev, Alexey V.; Grygorenko, Oleksandr O. (Synthesis, 2020)
A three-step approach to the synthesis of sp3-enriched β-fluoro sulfonyl chlorides starting from alkenes is reported. The method was successfully applied to a wide range of acyclic and cyclic substrates, bearing either an exocyclic or an endocyclic double bond. The procedure worked with a wide range of substrates and tolerated a number of functional and protecting groups. Moreover, the target cyclic compounds were obtained as single cis diastereomers on a multigram scale. The title compounds are promising building blocks for drug discovery that can be used to obtain sp3-enriched β-fluoro and α,β-unsaturated sulfonamides.
Keywords: organosulfur compounds; organofluorine compounds; oxidation; sulfonyl chlorides; building blocks